Innovations Developed in Universities – the Triple Helix Acting on Fuel Quality Monitoring - Silva, Sthefania Fernandes (2019)
Due to the Agência Nacional do Petróleo, Gás Natural e Biocombustíveis (ANP) demanding more effective methods in fuel compliance analysis, research has appeared in this area. Against the foregoing, the present article discusses the role of these researches, carried out by universities, as an insightful means of achieving such a demand. In particular, the research is focused on improving the methods of monitoring the quality of fuels in Brazil. The analysis is based on qualitative exploratory research, based on the survey of the levels of non-conformity of fuel quality published by ANP. Starting from the "triple helix" concept and the interaction between government-university-enterprise, is discussed the effect of laws to encourage innovation and success stories in the overflow of scientific production to the market. Data analysis shows that the public-private partnership combined with public policies related to innovation reduce the levels of non-compliance of gasoline, ethanol and diesel oil.